Observations of near surface wind speed, temperature and radiative budget at Dome C, Antarctic Plateau during 2005. Issue 1 (17th June 2013) - Argentini, Stefania; Pietroni, Ilaria; Mastrantonio, Giangiuseppe; Viola, Angelo P.; Dargaud, Guillaume; Petenko, Igor
Abstract The annual and diurnal behaviours of near surface wind speed, temperature, and the radiative budget at Concordia Station (Dome C) in different seasons are shown. The wind speed was lowest in summer when a daily cycle was also observed. The largest mean values were concurrent with boundary layer growth in the afternoon. In winter and spring the wind speed reached the highest mean values. Perturbations in the wind flow were due to warming events which occurred periodically at Dome C. The lowest temperatures were in April and at the end of August. The coreless winter behaviour was perturbed by warming events which in many cases produced an increase in temperature of c. 20°C. The average temperature profiles show permanent thermal inversion, with the exception of a few hours in the afternoons during the summer. The strongest ground-based thermal inversions were observed in the polar winter. The largest potential temperature gradients were limited to a 30–40 m deep layer close to the surface. The net radiation was negative almost all the time with the exception of the period from mid-December to mid-January.